Natural Hematite for Next‐Generation Solid Oxide Fuel Cells. (9th December 2015) - Wu, Yan; Xia, Chen; Zhang, Wei; Yang, Xiang; Bao, Zheng Yu; Li, Jiao Jun; Zhu, Bin
Abstract : Natural hematite ore is used as a novel electrolyte material for advanced solid oxide fuel cells (SOFCs). This hematite‐based system exhibits a maximum power density of 225 mW cm −2 at 600 °C and reaches 467 mW cm −2 when the hematite is mixed with perovskite‐structured La0.6 Sr0.4 Co0.2 Fe0.8 O3–δ . These results demonstrate that natural materials for next‐generation SOFCs can influence the multiutilization of natural resources, thereby affecting the environment and energy sustainability. Abstract : The natural hematite explored in this work for advanced solid oxide fuel cells (SOFCs) indicates new‐generation affordable SOFC products. This design and processing concept can be easily extended to other systems, and these natural mineral materials with desired functions and properties hold great promise for potential applications in the fields of energy and environmental science.